Fournier’s gangrene: a clinical profile of 30 cases - T., Kavya; Babu G., Rajashekara; C. S., Santhosh (International Surgery Journal, 2018)
Background: Fournier's gangrene is a rapidly progressive synergistic infection involving the perineal region and the scrotum and/or the penis. This study was conducted to know about the etiology and mode of presentation of Fournier’s gangrene and the impact of early and aggressive multimodality treatment in reduction in morbidity and mortality associated with this condition which is still considered to be significantly high. Methods: The medical records of 30 patients of Fournier's gangrene who presented to the hospital between May 2014 to June 2017 were retrospectively reviewed to analyze the presentation, progression and the outcome of the disease. Results: The study included a total of 30 male patients. The mean age was 57 years (range 38-72 years). The most common etiology was secondary to anorectal pathology (40%). The most common predisposing factor was noticed to be diabetes mellitus (73.34%). Pain and tenderness in the perineal region was present in most of the patients and scrotal involvement was seen in 66.67% of the patients. Fever was the most common prodromal condition seen in 93.33% all of which in turn were associated with tachycardia. Hyperleukocytosis was seen in 93.33% of patients except for one patient who was diagnosed to be retropositive on admission. The microbiological profile yielded polymicrobial culture report in 80% of the patients and monomicrobial in the rest with Escherichia coli being the most common organism isolated from 80% of the patients. All patients underwent adequate resuscitation, primary emergency debridement with parenteral antibiotic therapy. All the patients recovered after a mean hospital stay of 16.93 days (range 9-30 days). The mortality rate in present study was found to be 6.67%. Conclusions: In spite of the advancements in the field of medicine Fournier’s gangrene still remains a disease with questionable degree of morbidity and mortality and early detection and treatment with aggressive debridement seems to be the only way of obtaining a good prognosis in these patients.